2008
DOI: 10.1111/j.1365-2702.2007.02050.x
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of caring in a technological environment: critical care nurses’ experiences

Abstract: Experienced critical care nurses are able to transcend the obtrusive nature of technology to deliver expert caring to their patients. However, the journey to proficiency in technology is very demanding and novice nurses have difficulty in caring with technology. Relevance to clinical practice. It is recommended that more emphasis be placed on supporting, assisting and educating inexperienced nurses in the critical care area and that the use of technology in nursing be given serious consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 34 publications
2
72
0
Order By: Relevance
“…Empathy levels among the participants in our study were lower than that of nurse practitioners (Hojat et al , ). ICU nurses practice in a technological care environment, which could tend to dehumanize their work (McGrath, ) and reduce their level of empathy (Lützen et al , ). During the debriefing, study participants were made aware of how important empathy is for intensive care patients.…”
Section: Discussionmentioning
confidence: 99%
“…Empathy levels among the participants in our study were lower than that of nurse practitioners (Hojat et al , ). ICU nurses practice in a technological care environment, which could tend to dehumanize their work (McGrath, ) and reduce their level of empathy (Lützen et al , ). During the debriefing, study participants were made aware of how important empathy is for intensive care patients.…”
Section: Discussionmentioning
confidence: 99%
“…Technology often "inserts itself" between patients and nurses (O'Keefe-McCarthy, 2009, p. 786), despite attempts of experienced nurses to navigate it (McGrath, 2008). Nurses frequently view technologies that control medication in terms of their ability to control nurses' labor (Armstrong, Choiniere, & Day, 1993).…”
Section: Technology and Controlmentioning
confidence: 96%
“…Previous research has suggested that the presence of technology may distract nurses from the psychological care of patients (Hofhuis et al . , McGrath ). Lee () and Price (), in their respective qualitative studies, revealed that nurses perceive technology to place increased demands on their time, allowing less time in which to establish a nurse‐patient relationship and to be involved in personal care.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Kongsuwan and Locsin () suggested that technological mastery incorporates compassionate caring. Similarly, McGrath () identified that the nurse participants thought that excellence in nursing care was dependent on nurses' expertise and technological skill adding that technology enabled nurses to know their patients.…”
Section: Introductionmentioning
confidence: 99%